Design of hybrid power-to-power systems for continuous clean PV-based energy supply. (14th April 2021) - Crespi, Elena; Colbertaldo, Paolo; Guandalini, Giulio; Campanari, Stefano
Abstract: The increasing penetration of intermittent renewable sources, fostering power sector decarbonization, calls for the adoption of energy storage systems as an essential mean to improve local electricity exploitation, reducing the impact of distributed power generation on the electric grid. This work compares the use of hydrogen-based Power-to-Power systems, battery systems and hybrid hydrogen-battery systems to supply a constant 1 MWel load with electricity locally generated by a photovoltaic plant. A techno-economic optimization model is set up that optimizes the size and annual operation of the system components (photovoltaic field, electrolyzer, hydrogen storage tanks, fuel cell and batteries) with the objective of minimizing the annual average cost of electricity, while guaranteeing an imposed share of local renewable self-generation. Results show that, with the present values of investment costs and grid electricity prices, the installation of an energy storage system is not economically attractive by itself, whereas the installation of PV panels is beneficial in terms of costs, so that the baseline optimal solution consists of a 4.2 MWp solar field capable to self-generate 33% of the load annually. For imposed shares of self-generation above 40%, decoupling generation and consumption becomes necessary. The use of batteries is slightly less expensive than the use of hydrogen storage systems up to a 92% self-generation rate. Above this threshold, seasonal storage becomes predominant and hybrid storage becomes cheaper than batteries. The sale of excess electricity is always important to support the plant economics, and a sale price reduction sensibly impacts the results. Hydrogen storage becomes more competitive when the need for medium and long terms energy shift increases, e.g. in case of having a cap on the available PV capacity. Highlights: A cost optimization model of a PV + hybrid energy storage system was developed. The hybrid energy storage system comprises hydrogen-based P2P and battery storage. Above 40% self-generation, energy storage becomes mandatory. Long-term energy shift makes hydrogen-P2P systems more competitive for storage.